Assessment of Volume Status Using Body Composition Monitor for Blood Pressure Control in Patients Undergoing Maintenance Hemodialysis: A Randomized Controlled Trial - Dhakal, Niraj; Sapkota, Nisha K; Sigdel, Mahesh R (Journal of Institute of Medicine Nepal, 2023)
Introduction Optimal fluid balance and blood pressure control have been shown to improve outcomes in hemodialysis population. We investigated the effectiveness of body composition monitor (BCM) to target dry weight in maintenance hemodialysis (MHD) patients for blood pressure (BP) control and intradialytic adverse events. Methods A total of 61 consenting adults under MHD were randomly allocated into either BCM group or Clinical Method group. Target dry weight was set every 4-weekly based on BCM report or clinical assessment; dry weight was adjusted with 200-500 ml/session reduction or increment of ultrafiltration in addition to interdialytic weight gain. Outcomes were analyzed in terms of BP control, anti-hypertensive medicine score, and intradialytic adverse events. Results During 12 weeks of study period, systolic blood pressure (p < 0.001), diastolic blood pressure (p = 0.01) and mean arterial pressure (p < 0.001) significantly decreased from baseline in BCM group but there were no significant changes in Clinical Method group. Lower blood pressure was achieved in BCM group as compared to Clinical Method group. There was a significant decrease from baseline in anti-hypertensive medicine score in the BCM group (p < 0.001) but not in the clinical method group (p = 0.34). There were significantly fewer events of cramps in the BCM group as compared to the Clinical Method group (p = 0.04). Conclusion BCM guided volume management in MHD patients was more effective than volume management based on clinical judgment only in controlling blood pressure and decreasing anti-hypertensive medicine burden and intradialytic cramps.